Kesiapan Masyarakat Dalam Pemilihan Kepala Daerah Langsung - Leo Agustino (Centre for Public Policy and Management Studies, 2004)
The system of Directly Regional Head Election (Pilkada) will be held in Indonesia constitute the expected process to enhance the quality of democratization in this country. Nevertheless there is still a hesitation related to opinion about unreadiness of public to be involved in pilkada. This paper put the public Indonesian factual practices forward to neutralize the hesitation. There are some theoritical approach explained as tool of analysis to predict the active actualization of voters behavior in Indonesia.Kata kunci : pilkada, demokratisasi, partisipasi politik, kesiapan pemilih dan prilaku pemilih.